Structural Policy: Towards a New Investment Model of Economic Growth - O. S. Sukharev (Финансы: теория и практика)
The article examines structural policy as a tool for developing a new economic growth model in Russia. The author considers the conditions of economic growth based on increased investment. The purpose of the article is to determine the current characteristics of the Russian economy structural dynamics by the components of GDP and basic sectors. The basic sectors of the current investment structure have been assessed — processing sector and transactional and raw materials sector — and the directions for further development have been specified. The research methodology consists of: structural analysis of GDP and sectoral dynamics; the received and applied “structural formula” of assessing the contribution of the system elements to economic growth; formulated simple optimization models and a numerical optimization method (gradient projection method). The method of empirical and statistical estimates has also been used. Optimization models have made it possible to demonstrate the solution to the problem of distributing investments between the sectors with a target function for maximum profit and minimum risk. The analysis of growth and the conditions for economic growth obtained by the model-analytical method — in terms of the rate of change in oil prices and the exchange rate — allowed us to empirically show periods of growth and recession in the economy. They depend on the growth rate of oil prices and the devaluation of the rouble. This approach, with further use of econometric models linking macroparameters, will make it possible to evaluate the effect of changes in structural parameters on economic growth. The overall result of the study is as follows: the intensification of investments is insufficient to organize the investment model of economic growth in Russia. The stimulation of gross consumption and a change in the structure of investments are required. It is necessary to reduce the gap between the sectors by risk mitigation. External factors affecting the economic growth in Russia (oil prices, currency inflows) must be eliminated by changing the structure, including the sensitivity increase of its elements to macroeconomic policy instruments, and differentiating sectoral policy measures considering the positive impact on the contribution of GDP components and sectors of money growth and inflation.